100 science experiments - Andrews, Georgina; Wray, Zoë. Lalonde, Tom Knighton, Kate Lovell, Katie (Usborne London, 2012)
"This action-packed collection of science experiments combines hands-on fun and scientific investigation. See the results for yourself and then find out what's really going on by discovering the science behind it all."--Back cover